Re-envisioning Indonesia’s Local Wisdom-Based Curriculum Policy: The Elsie Ripley Clapp Model Approach - Utari, Tria Ina; Maisyaroh, Maisyaroh; Nurabadi, Ahmad; Hung, Min-Ling (Jurnal Pendidikan Progresif, 2024)
Re-envisioning Indonesia's Local Wisdom-Based Curriculum Policy: The Elsie Ripley Clapp Model Approach. Objective: The local wisdom-based curriculum policy is a concept that can address problems for indigenous communities. The purpose of this research is to re-examine Indonesia's local wisdom-based curriculum policy through the Clapp model approach for marginal sub-ethnic groups. Method: The research method used is a literature review of findings from articles on indigenous curriculum policy, indigenous education, and indigenous community school. Results: The Elsie Ripley Clapp model approach is rooted in the value of the school as a democratic space and a commitment to social justice that unites various social classes, focusing on local history, geography, and economy. Conclusion: The application of Elsie Ripley Clapp's progressive pedagogical ideology in curriculum development practices in the 1920s-1930s at Ballard School in Kentucky and Arthurdale School in Virginia can serve as a conceptual approach to curriculum policy in Indonesian social education studies. This involves rethinking curriculum policy for community schools in marginal areas that are socio-geographically distinct and focusing on the communal values of society. Keywords: curriculum policy, local wisdom, clapp model, community school, Indonesia.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202496